CONCEPTS OF LANGUAGE POLICY AND LANGUAGE PLANNİNG - Elchin IBRAHIMOV (Progress in Science, 2023)
Although the terms “language policy” and “language planning” are considered new concepts, they have a long history as a sociolinguistic phenomenon. Researchers in the field of language policy and language planning have not been able to agree on a single term to express this concept. As mentioned above, the terms “language policy” and “language planning” are sometimes used as different and sometimes as the same concept. Regulation and regulation of language is a concept that covers all the conscious activities related to the structure, position, use and function of languages. However, this concept expressed by different terms such as “language regulation”, “language policy”, “language planning” reflects multifaceted activities in different processes and directions. These vary depending on whether the intervention consists of concrete ideas or an abstract action plan, whether the mentioned activities are aimed at language norms or the status of the language, as well as the nature of influencing its progress and at what stage. The first stage of language regulation is the evaluation process aimed at determining language and language-society problems. At this stage, the emerging problems are considered. The next stage, that is, language policy, is the most concrete stage of an activity aimed at the regulatory process, which consists of defining goals.